Learning PHP, MySQL, JavaScript, CSS & HTML5 - Nixon, Robin, 1961- (O'Reilly Media, 2014)
Build interactive, data-driven websites with the potent combination of open-source technologies and web standards, even if you only have basic HTML knowledge. With this popular hands-on guide, you'll tackle dynamic web programming with the help of today's core technologies: PHP, MySQL, JavaScript, CSS, and HTML5. Explore each technology separately, learn how to use them together, and pick up valuable web programming practices along the way. At the end of the book, you'll put everything together to build a fully functional social networking site. Learn PHP in-depth, along with the basics of object-oriented programming Explore MySQL, from database structure to complex queries Create dynamic PHP web pages that tailor themselves to the user Manage cookies and sessions, and maintain a high level of security Master the JavaScript language and use it to create interactive web pages Use Ajax calls for background browser/server communication Acquire CSS2 & CSS3 skills for professionally styling your web pages Implement all the new HTML5 features, including geolocation, audio, video, and the canvas.